Ocular findings in Loeys-Dietz syndrome. Issue 8 (16th November 2017) - Busch, Catharina; Voitl, Robert; Goergen, Barbara; Zemojtel, Tomasz; Gehle, Petra; Salchow, Daniel J
Abstract : Background: Loeys-Dietz syndrome (LDS), an autosomal-dominant connective tissue disorder, is characterised by systemic manifestations including arterial aneurysm and craniofacial dysmorphologies. Although ocular involvement in LDS has been reported, detailed information on those manifestations is lacking. Methods: Retrospective chart review of patients with diagnosed LDS and comparison with age-matched control patients. Results: Mean age was 37.8±14.6 years (patients with LDS) and 38.4±13.5 years (controls). Patients with LDS less frequently had iris transillumination, cataract and glaucoma compared with controls. Scleral and retinal vascular abnormalities were not found in any of the LDS eyes. Ectopia lentis was found in one patient with LDS. The eyes of patients with LDS tended to be more myopic (spherical equivalent, −2.47±2.70 dioptres (dpt) vs −1.30±2.96dpt (controls); P=0.08) and longer (24.6±1.7mm vs 24.1±1.5mm (controls); P=0.10). Central corneal thickness was significantly reduced in LDS eyes (521±48µm vs 542±37µm (controls); P=0.02). Corneal curvature (43.06±1.90dpt (LDS) versus 43.00±1.37dpt (controls); P=0.72) and interpupillary distance (65.0±6.0mm (LDS) vs 64.3±4.8mm (controls); P=0.66) did not differ significantly between both groups. Visual acuity was similar between both groups (0.03±0.09logarithm of the minimum angle of resolution (logMAR) for LDS eyes and 0.05±0.17logMAR for control eyes, P=0.47). Conclusions: Ocular features of LDS include decreased central corneal thickness and mild myopia. Ectopia lentis may be slightly more common than in controls but appears less common than in Marfan syndrome. Hypertelorism, scleral and retinal vascular abnormalities were not features of LDS.